Drivers of decoupling and recoupling of crop and livestock systems at farm and territorial scales - Rachael D. Garrett (Resilience Alliance, 2020)
Crop and livestock production have become spatially decoupled in existing commercial agricultural regimes throughout the world. These segregated high input production systems contribute to some of the world's most pressing sustainability challenges, including climate change, nutrient imbalances, water pollution, biodiversity decline, and increasingly precarious rural livelihoods. There is substantial evidence that by closing the loop in nutrient and energy cycles, recoupling crop and livestock systems at farm and territorial scales can help reduce the environmental externalities associated with conventional commercial farming without declines in profitability or yields. Yet such "integrated" crop and livestock systems remain rare as a proportion of global agricultural area. Based on an interdisciplinary workshop and additional literature review, we provide a comprehensive historical and international perspective on why integrated crop and livestock systems have declined in most regions and what conditions have fostered their persistence and reemergence in others. We also identify levers for encouraging the reemergence of integrated crop and livestock systems worldwide. We conclude that a major disruption of the current regime would be needed to foster crop-livestock reintegration, including a redesign of research programs, credit systems, payments for ecosystem services, insurance programs, and food safety regulations to focus on whole farm outcomes and the creation of a circular economy. An expansion of the number of integrated crop and livestock systems field trials and demonstrations and efforts to brand integrated crop and livestock systems as a form of sustainable agriculture through the development of eco-labels could also improve adoption, but would likely be unsuccessful at encouraging wide-scale change without a more radical transformation of the research and policy landscape.